Cultural Mediation and Democratizing Access to Culture inChile: An Analysis of Inclusive Educational Strategies for DeafPeople at the Museum of Contemporary Art - Villarroel Arredondo, Antonia (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
This article aims to reflect on how society evolves regarding the integration of Chilean Sign Language (ChSL) within the different forms of citizen participation, with a particular focus on cultural practices. Through a case study of the cultural mediation work carried out by the Education Unit of the Museum of Contemporary Art (MAC) in Santiago, the study analyzes how the articulation of different disciplines contributes to democratizing access to culture. It does so by looking into an educational program designed to integrate people with disabilities, especially those with hearing impairment.Based on cultural studies and communications, this piece develops a critical reflection on the importance of new ideas and questions about the integration of different languages, communication bridges, and encounter settings for more inclusion and diversification of culture users. The study proposes cultural practice as a way of living and exercising active citizenship, as well as fostering a sense of belonging and community-building. It underscores the relevance of communication strategies to gather different people together, without reinforcing physical distinctions. The essay concludes by asserting access to culture as a fundamental human right.
Keywords: Cultural mediation; Cultural democratization; Accessibility; Inclusion; Hearing impairment